(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article expressed views on some threats characteristic of the transition period in Uzbekistan, the fight against religious and political extremism carried out to seize power, analyzed the essence of political reforms carried out on the basis of the ideas of national ideology, capable of countering it. Based on the initial experience of reforming the country, the basic principles of further development of society have been developed. They coped with the task of strengthening stability and restoring society. The article is devoted to the analysis of the history of these processes and their peculiarities.